Juvenile thyrotoxicosis; can we do better?. Issue 8 (21st July 2004) - Birrell, G; Cheetham, T
Abstract : Thyrotoxicosis remains a frustrating condition for the young person, family, and health professionals involved. The associated symptoms do not always suggest thyroid disease and patients can be unwell for many months before the diagnosis is made. The antithyroid drug regimen used to treat children and adolescents with thyrotoxicosis varies from one unit to another and yet the potentially life threatening side effects and remission rates post-treatment may be related to the regimen used. Most patients with thyrotoxicosis will need many years of drug therapy if the thyroid gland is not removed surgically or destroyed by radioiodine. Even "definitive" treatment will typically necessitate thyroxine replacement for life.